Empowerment of Silaban margu arts sanggar as crafts of Batak Toba music tradition instruments in Huta Sitangkuban village Siponjot Kecamatan Lintong Ni Huta district Humbang Hasundutan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Sanggar Seni Silaban Margu is an organization in Huta Sitangkuban, Siponjot Village, Lintong Ni Huta Subdistrict, Humbang Hasundutan Regency. The presence of Sanggar Seni Silaban Margu, has helped increase the activities of citizens through the production of a numerous traditional Batak Toba musical instruments and has also marketed them for both locally and nationally. They also carry out routine training in playing music, thus providing an opportunity for the Huta Sitangkuban community to understand and develop their own arts. The problem faced at this time is that Silaban Margu has not implemented productive time management and good human resource management as well as planned work methods that can be applied to provide high quality and maximum production results. The craftsmen of these musical instruments have not yet applied the method of processing wood from the remnants of making musical instruments that could actually be used to be processed into other artistic creativity items. The implementation of community service activities is carried out in two main forms, namely socialization and assistance. In addition, we also provided assistance with work equipment to facilitate better production access. Meanwhile in based on ideas, the we provided an understanding of how to manage time as well as human resources, so that the duration of productive work hours and working methods of musical instrument craftsmen can be maximized. The dedication team provided the craftsmen with the idea of ​​processing existing wood, not only for making musical instruments, but the rest of the production was then made into other artistic creations, which could be used for daily life needs. These community service activities had become the basis idea for planning the ‘Desa Binaan’